2007
DOI: 10.1007/s00108-006-1750-4
|View full text |Cite
|
Sign up to set email alerts
|

Angina Pectoris und ST-Hebungen nach Chemotherapie mit 5-FU

Abstract: We report on the case of a 64 year old male who received chemotherapy for a metastatic squamous cell carcinoma of the oropharynx. The chemotherapeutic regimen consisted of 5-fluorouracil (5-FU) and cisplatin. Six hours after completion of the first 24 h continuous infusion of 5-FU, the patient developed severe chest pain accompanied by vegetative symptoms and a pronounced ST-elevation of the precordial leads. Under the suspicion of an acute anterior myocardial infarction an immediate coronary angiogram was per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 12 publications
0
8
1
Order By: Relevance
“… 72 , 73 Amongst patients suspected of having 5-FU-related cardiotoxicity, vasospasm was not demonstrated on pharmacologic provocation with the alkaloid ergonovine, 74 an agent that has previously been used to assess coronary vasomotor function through its action on smooth muscle serotonergic receptors, which in turn leads to muscle contraction and vasoconstriction under physiologic conditions. 75 Furthermore, in one study of patients who reported angina in response to a 5-FU challenge who had ECG changes suggestive of ischemia, those who underwent concurrent echocardiography were shown to have global akinesia, incompatible with a characteristic territorial distribution of a major coronary artery. 5 Despite the systemic distribution of 5-FU, multivessel coronary vasospasm is uncommon in patients receiving 5-FU.…”
Section: Potential Mechanisms Leading To 5-fu-related Cardiotoxicitymentioning
confidence: 99%
“… 72 , 73 Amongst patients suspected of having 5-FU-related cardiotoxicity, vasospasm was not demonstrated on pharmacologic provocation with the alkaloid ergonovine, 74 an agent that has previously been used to assess coronary vasomotor function through its action on smooth muscle serotonergic receptors, which in turn leads to muscle contraction and vasoconstriction under physiologic conditions. 75 Furthermore, in one study of patients who reported angina in response to a 5-FU challenge who had ECG changes suggestive of ischemia, those who underwent concurrent echocardiography were shown to have global akinesia, incompatible with a characteristic territorial distribution of a major coronary artery. 5 Despite the systemic distribution of 5-FU, multivessel coronary vasospasm is uncommon in patients receiving 5-FU.…”
Section: Potential Mechanisms Leading To 5-fu-related Cardiotoxicitymentioning
confidence: 99%
“…The patient suffered from 2-vessel coronary artery disease and was treated with PCI and implantation of 2 drug-eluting stents following left heart catheterization [6]. In contrast, after systemic chemotherapy with intravenous 5-FU, a 64-year-old male patient developed typical angina pectoris with ST segment elevations in V1-V4 but without any increase in cardiac enzymes, as reported by Spencker et al [9]. The most likely cause was a complete vasospasm of the LAD coronary artery with consecutive complete occlusion of the vessel, which diminished after intracoronary administration of nitroglycerin (0.2 mg) [9].…”
Section: Discussionmentioning
confidence: 76%
“…In contrast, after systemic chemotherapy with intravenous 5-FU, a 64-year-old male patient developed typical angina pectoris with ST segment elevations in V1-V4 but without any increase in cardiac enzymes, as reported by Spencker et al [9]. The most likely cause was a complete vasospasm of the LAD coronary artery with consecutive complete occlusion of the vessel, which diminished after intracoronary administration of nitroglycerin (0.2 mg) [9]. For oxaliplatin, which was used in the present patient, data on events mimicking acute coronary syndromes are rare.…”
Section: Discussionmentioning
confidence: 90%
“…Cancer chemotherapy has also been associated with vasospastic angina [28][29][30][31][32][33]. Indeed our patient, who had previously been reported allergic to iodinated contrast media, developed allergic angina and coronary vasospasm after therapy with cisplatin and cyclophosphamide.…”
Section: Discussionmentioning
confidence: 78%